Suicide interventions for American Indian and Alaska Native populations: A systematic review of outcomes - Tony V Pham; Anna Kawennison Fetter; Andrea Wiglesworth; LittleDove F. Rey; Micah L. Prairie Chicken; Michael Azarani; Amy Riegelman; Joseph P. Gone (Elsevier, 2021)
Objective: A 2018 Center for Disease Control and Prevention report estimated that 22.1 per 100,000 American Indian/Alaska Native (AI/AN) individuals died by suicide, much higher than the overall U.S. rate of 14.2. To understand how to remedy this problem, we performed a systematic review in response to the following question: "What interventions work to prevent AI/AN suicide?" Method: We adopted a broad inclusionary stance while searching, screening, and extracting data. Our search strategy yielded 1605 unique citations, and after screening 28 items met the set criteria. Results: While participants from each study reported an improvement on at least one targeted measure, particularly along community-driven outcome measures, several methodological modifications arose to meet the ideals of both practice- and evidence-based research. For example, only 11 studies featured assessments that measured changes in direct suicide outcomes. Among these 11 studies, only four featured either a randomized or a non-randomized controlled trial. Furthermore, only one intervention produced consistent outcomes across several studies. Nevertheless, the results from our reviewed corpus were methodologically innovative and suggest an overall benefit to AI/AN communities. Conclusions: The case for these interventions could be augmented through a variety of methodological advancements. Thus, we propose that future studies dismantle their interventions into underlying processes, evaluate these processes using direct, standardized measures of suicidal behavior, and incentivize AI/AN recruitment into research trials outside of Indian Country.